Review Article on purification of polluted water by Ayurveda: Ayurvedic Approach - Jangid, Madhu; Firoda, Priyanka (International Research Journal of Ayurveda & Yoga, 2021)
Water is essential need of human being. Safety and purity of water is main concern of today’s era. Water today we use comes from various sources. As there are different sources, quality, purity of water changes. Water is seen contaminated by toxic elements like arsenic, fluorides, microbes etc. leads to health hazards. Though there are many advanced techniques for purification of water at different levels but these all are very expensive, not at level of common man and also some techniques lead to depletion of essential elements of water. As per ayurveda treatment of water with various herbs helps in de contaminating the water without depletion of essential elements and also is very cost effective. Though various researches should be done for establishment of ayurvedic treatment of water. By this paper we share an idea of ayurvedic treatment of impure water.